The Big Five Personality and Perception of the Career Barriers of Male Prisoners: moderated Mediating Effect Models - Wang, Peng (Crime & delinquency, 2023)
Prisoners’ employment has received widespread attention from society. In this study, based on career construction theory and social cognitive career theory, 300 male prisoners were selected as the research sample, and questionnaires were used for data collection. The results show that in the relationships between extroversion, openness, neuroticism, and perception of career barriers, and prisoners’ career adaptability plays a mediating role. When extroversion, openness, and neuroticism are predictor variables, the socioeconomic status of prisoners plays a moderating role in the predictive effect of career adaptability on the perception of career barriers. Specifically, compared with individuals with low and medium socioeconomic statuses, the negative effect of career adaptability on the perception of career barriers was stronger at high socioeconomic status levels.